Research Progress on Monitoring and Regulation of Closed Solid-State Fermentation Systems - ZHANG Nan, CHENG Siyuan, YU Yongjian, DOU Shuaiwei, LIU Jiaxin, TANG Ruijun, ZHU Yuanyuan, YU Zhen (Shipin Kexue)
A closed solid-state fermentation system refers to a system that automatically and intelligently completes solid-state fermentation under closed and controllable conditions to stabilize product quality, reduce labor intensity and improve intelligence level. In recent years, with the transformation and upgrading of the traditional brewing industry and with the increasingly urgent need to promote intelligent manufacturing, the research and development of closed solid-state fermentation systems have attracted more and more attention from the industry and researchers. In this paper, the monitoring methods for closed solid-state fermentation systems are reviewed from three perspectives: the application of various monitoring equipment and methods, the development of various mathematical models and control strategies, and the optimization of monitoring equipment using various control strategies. In addition, this review introduces the regulation strategies for closed solid-state fermentation systems in order to provide a theoretical basis for improving existing solid-state fermentation systems and developing new ones in the future.